“RAYA AND THE LAST DRAGON” ANIMATION FILM: A SOURCE OF INSPIRATION FOR THE DEVELOPMENT OF INDONESIA'S CULTURE-BASED CREATIVE INDUSTRY - Yono, Sri; Satiyoko, Yohanes Adhi; Sumiyardana, Kustri; Wibowo, Eko Cahyo Kusumo; Suwondo, Tirto (Widyaparwa, 2024)
The success of the animated film "Raya and The Last Dragon" which blends Southeast Asian culture is one proof of the new power of the economy that relies on creativity. This study aims to analyze aspects of art-literature-culture in the film that have the potential to be an inspiration for the development of culture-based creative industries (economy) in Indonesia. Using the basic concepts of creative economy theory and cultural anthropology, data collection in this descriptive-qualitative study is carried out by document study methods. The main data source of this study is the animated film "Raya and The Last Dragon" and secondary data sources are obtained from written, audio, and video materials. The data collected in this study refers to the scope of culture, namely ideas or opinion, cultural activities, and the results of cultural creativity contained in this animated film. The data that have been identified and classified are further analyzed using the concepts of creative (industrial) economic theory and cultural anthropology. The results of the study show that the work process and aspects of art-culture such as content creation based on local mythology, introduction of cultural values through stories, multi-cultural content creation, cultural tourism, cultural collaboration and creative industries, creative training, and innovation are important factors that inspire creators to develop culture-based creative industries in Indonesia. This study contributes to the development of interdisciplinary studies between humanities (art-culture-literature) and economics. Kesuksesan film animasi “Raya and The Last Dragon” yang meramu budaya Asia Tenggara menjadi salah satu bukti kekuatan baru ekonomi yang bertumpu pada kreativitas. Kajian ini bertujuan menganalisis aspek-aspek seni-sastra-budaya dalam film tersebut yang berpotensi menjadi inspirasi bagi pengembangan industri (ekonomi) kreatif berbasis budaya di Indonesia. Dengan menggunakan konsep dasar teori ekonomi kreatif dan antropologi budaya, pengumpulan data dalam kajian deskriptif-kualitatif ini dilakukan dengan metode studi dokumen. Sumber data utama kajian ini adalah film animasi “Raya and The Last Dragon” dan sumber data sekunder diperoleh dari bahan-bahan tertulis, audio, dan video. Data yang dikumpulkan dalam kajian ini merujuk pada ruang lingkup budaya, yaitu ide atau gagasan, aktivitas budaya, dan hasil dari kreativitas budaya yang terdapat dalam film animasi ini. Data yang telah diidentifikasi dan diklasifikasi selanjutnya dianalisis dengan menggunakan konsep teori ekonomi (industri) kreatif dan antropologi budaya. Hasil kajian menunjukkan bahwa proses kerja dan aspek-aspek seni-budaya seperti pembuatan konten berbasis mitologi lokal, pengenalan nilai budaya melalui cerita, pembuatan konten multi budaya, pariwisata budaya, kolaborasi budaya dan industri kreatif, pelatihan kreatif, dan inovasi menjadi faktor penting yang menginspirasi kreator untuk mengembangkan industri kreatif berbasis budaya di Indonesia. Kajian ini berkontribusi bagi pengembangan kajian interdisipliner antara humaniora (seni-budaya-sastra) dan ekonomi.